Bio-pretreatment promote hydrolysis and acidification of oilseed rape straw: Roles of fermentation broth and micro-oxygen. (July 2020) - Wang, Chuqiao; Zhang, Jiajie; Hu, Fengping; Zhang, Shuai; Lu, Ji; Liu, Shuai
Graphical abstract: Highlights: Fermentation broth and micro-oxygen could enhance the degradation of ORS. Maximum biodegradation rates of CHL were gained at 120 mL/gVS/d oxygen load. Fermentation broth could effectively decrease the functional groups related to lignin. Abstract: Oilseed rape straw (ORS) is capable of producing renewable energy. However, cellulose, hemicellulose and lignin are intertwined together in ORS, which makes it difficult for anaerobic digestion (AD). Hence, pretreatment is the key factor in reducing the rate-limiting step of AD. This study reports that the pretreatment combined fermentation broth and micro-oxygen could enhance the degradation of ORS. The maximum biodegradation ratios of cellulose, hemicellulose, and lignin (CHL) were 20.6%, 18.1%, and 24.7%, respectively, at 120 mL/gVS/d oxygen load. The maximum volatile fatty acids and soluble chemical oxygen demand of hydrolysis and acidification of the pretreated groups were significantly higher than that of the control groups. Microorganisms in the fermentation broth at micro-aerobic conditions led to the reduction of CHL content, and altered the structure of ORS. The fermentation broth bio-pretreatment could effectively decrease the functional groups related to lignin.